Andrographis Paniculata in the Treatment of Upper Respiratory Tract Infections - Annisa Septrina (HM Publisher, 2022)
Andrographis paniculata is a species of Andrographis paniculata (Burm. F) The herbaceous plant Nees, sometimes known as